Development of a proactive approach to determining the transformation of organizational structures of enterprises - Hetman, Olha; Kryvoruchko, Hanna; Chupyr, Olena; Avanesova, Nina; Fesun, Iryna (Technology audit and production reserves, 2025)
The object of research is the process of transforming the configurations of structures. It is known that the timeliness of making a decision on the transformation of the configuration depends on the type of external environment, which is determined according to the level of influence of its main characteristics on the enterprise, while each type of environment corresponds to a specific configuration. Untimely determination of trends in the change of the influence of the external environment leads to untimely transformation of the enterprise and the negative consequences associated with it. This is the problem that was solved in the work. The study is aimed at developing a proactive approach to the transformation of the configurations of structures, which takes into account the assessment of the rate of change in the influence of external factors on organizations and is a sequence in the implementation of structural transformation. The issue of proper structuring concerns enterprises operating in various sectors of the economy, including industry, agriculture, utilities, etc. The article presents a developed matrix for determining the directions of structural transformation and the main stages of a proactive approach to the transformation of structures. The value of the study lies in the fact that a proactive approach allows to identify possible structural problems in advance, make changes, and prevent the decline of a company at any stage of its life cycle. According to the results of the analysis, taking into account the change in the influence of external factors, only 3 percent of enterprises experienced decline within five years of existence (compared to those that did not change the management structure, this figure is 45 percent). The proactive approach can be applied regardless of the age of the organization, industry, geographical location, or market.